Marketing Strategy of Telkom Makassar Education Area Through Social Media Platforms in Influencing Prospective Students' Decision-Making - Adhytia Adhyaksa; Ignasius Liliek Senaharjanta (Syntax Corporation, 2026)
The development of social media as a digital communication medium has transformed marketing strategies in educational institutions. Schools no longer rely solely on conventional promotion but increasingly utilize social media to build institutional image, enhance visibility, and influence prospective students’ decision-making processes. SMK Telkom Makassar, a technology-based vocational school, uses social media—particularly Instagram—as part of its marketing communication strategy to engage Generation Z audiences. This study aims to analyze the social media strategy implemented by SMK Telkom Makassar and examine its role in influencing prospective students’ decision-making process, from problem recognition to post-decision evaluation. The research employs a qualitative approach, with data collected through social media content observation and interviews with relevant stakeholders. Data analysis focuses on digital communication aspects such as interaction and trendiness, and relates them to the stages of the consumer decision-making process. The findings indicate that SMK Telkom Makassar’s social media strategy plays a significant role in building brand awareness, providing accessible information, and strengthening prospective students’ confidence in choosing the school. The interaction strategy is reflected in two-way communication with audiences, although consistency still needs improvement. Meanwhile, the trendiness strategy is demonstrated through content that follows popular trends among Generation Z, effectively increasing visibility and reinforcing the school’s image as a modern and adaptive institution. Overall, social media functions not only as a promotional tool but also as an integral component of the school’s marketing communication strategy.